A STUDY OF VARIOUS WAYS OF ENGLISH LANGUAGE TEACHING METHODS IN RURAL AREAS - Ch Aparna, Dr. Priti Koolwal (Knowledgeable Research A Multidisciplinary Journal, 2025)
We live in a global world where our existence depends solely on our felicity of using English most often. Thus, getting well versed in English has become quite mandatory. While this does not pose a problem in metropolitan cities and towns, people in rural areas lack the skills to converse in English. There is still a major chunk of civilization devoid of the developments in terms of language and technology. English teachers teaching in rural areas often face the non-availability of required technical support and relevant atmosphere to teach English effectively. It is here that the role of innovative teachers becomes quite essential. An effective teacher, despite having limited resources, can prove himself as a tool. The present paper examines various resources and tools that can prove beneficial in teaching English as a foreign language. It will also throw light on the advantages and disadvantages of using teaching aids and will discover ways of how our pedagogical styles may work wonders at times. It has to be realized that despite all cacophony, it is ultimately the man who has to master the machines. Teaching is not only about the introduction of innovative technology but is also the desire to be created amongst our students. This desire ultimately converted into action can prompt an effective teacher to play a pivotal role in the entire process. The mere mention of teacher in a rural area reminds us of the teacher in Oliver Goldsmith’s poem “The Village Schoolmaster” whose ‘one small head could carry all he knew’. Things have changed today with the advances of science and the expectations of the global world. Today we need to have specialist teachers in every subject even in rural areas. This is because of the increased level of competition and the anxiety to survive and sustain in a fast-changing world. Knowledge of English today has become a sine-qua non for getting a coveted job and hence the importance of English teaching and learning has become manifold. As regards English teachers, their roles are not confined now to a hard task master but they are expected to be facilitator, a trainer, a counselor, a manager and a supervisor. There has been a transformation from ‘talk and chalk’ and teachers today have moved from BALL to CALL and now to MALL